2017
DOI: 10.1016/j.jaim.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of panchakarma and Ayurvedic treatment in postpartum rheumatoid arthritis ( amavata ): A case study

Abstract: Dream of a mother is to get involved actively in upbringing of child, which is impeded if she is suffering from painful condition like rheumatoid arthritis (RA) in postpartum phase. It causes physical incapacity and psychological trauma as well. Present case is a patient who developed RA one month after full term delivery by caesarean section. In view of symptoms, she was diagnosed as case of amavata. She received Ayurvedic treatment – Simhanada guggulu, Pratapalankeshwara rasa, Dashamoola katutraya kashaya an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…Many research articles have proved the efficacy of Ayurvedic drugs for the treatment of Rheumatoid arthritis. [11][12][13][14][15][16] In another study the GC MS analysis of Sahacharadi kashayam was reported showing the presence of the following molecules such as Heptanediamide, N,N'-di-benzoyloxy-Benzoic acid, Phenol, 2-methoxy-4-(1-propenyl), Eugenol, Tetradecanoic acid, 3-Decanone, 1-(4-hydroxy-3-methoxyphenyl)-(Gingerol), Abietic acid, 3-(6-Hydroxy-3,7-dimethyl-octa-2,7-dienyl)-4methoxyphenol, 5H-Cyclopropa [3,4] In yet another report Sahacharadi kashayam was reported to have very good antioxidant properties. 18 Many research articles have proved the efficacy of Ayurvedic drugs for the treatment of Rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Many research articles have proved the efficacy of Ayurvedic drugs for the treatment of Rheumatoid arthritis. [11][12][13][14][15][16] In another study the GC MS analysis of Sahacharadi kashayam was reported showing the presence of the following molecules such as Heptanediamide, N,N'-di-benzoyloxy-Benzoic acid, Phenol, 2-methoxy-4-(1-propenyl), Eugenol, Tetradecanoic acid, 3-Decanone, 1-(4-hydroxy-3-methoxyphenyl)-(Gingerol), Abietic acid, 3-(6-Hydroxy-3,7-dimethyl-octa-2,7-dienyl)-4methoxyphenol, 5H-Cyclopropa [3,4] In yet another report Sahacharadi kashayam was reported to have very good antioxidant properties. 18 Many research articles have proved the efficacy of Ayurvedic drugs for the treatment of Rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…After a 4-month course of treatment with oral herbs, application of medicated oil, swedana (sweating therapy) of the whole body in a wooden steam chamber, and kala basti (medicated enema), she experienced an improvement in pain, swelling and stiffness, was able to discontinue oral analgesics and normalized her rheumatoid arthritis titer. The breastfeeding neonate appeared to be reaching appropriate milestones with no adverse effects 5…”
Section: Ayurveda In the Preconception Periodmentioning
confidence: 94%
“…The breastfeeding neonate appeared to be reaching appropriate milestones with no adverse effects. 5 In the Ayurveda and Women's Health conference 6 presented in 2016, Dr Rosy Mann, an Ayurvedic practitioner, and faculty at the Kripalu School of Ayurveda provides guidance regarding preparing for conception. She reports that there are 4 main factors that support a healthy conception.…”
Section: Introduction: Ayurveda and Its Practicesmentioning
confidence: 99%
“…Therapeutische Optionen umfassen Vaman (Erbrechen), Virechan (Abführen), Basti (Einlauf mit einem Kräuterpräparat), Nasaya (Nasenreinigung) und Raktamoksha (Aderlass). In unserer Region wird aufgrund der Aspirationsgefahr das Erbrechen nur selten provoziert 2 .…”
Section: Behandlungsformenunclassified
“…Therapeutische Optionen umfassen Vaman (Erbrechen), Virechan (Abführen), Basti (Einlauf mit einem Kräuterpräparat), Nasaya (Nasenreinigung) und Raktamoksha (Aderlass). In unserer Region wird aufgrund der Aspirationsgefahr das Erbrechen nur selten provoziert[2].Zur Ausleitung bei hyperurikämieassoziierten Syndromen wird v. a. das Abführen zur Reinigung von Pitta und Ama eingesetzt, während insgesamt bei Schmerzen (bevorzugt bei Dorsalgien) auf Einläufe mit Sesamöl (ggf. unter Zusatz von Beinwell) oder Milch zurückgegriffen wird.…”
unclassified